Implications of a Soy-Based Diet for Animal Models - Dhot, Justine (Int J Mol Sci, 2021)
The use of animal models in fundamental or pre-clinical research remains an absolute requirement for understanding human pathologies and developing new drugs. In order to transpose these results into clinical practice, many parameters must be taken into account to limit bias. Attention has recently been focused on the sex, age or even strain of each animal, but the impact of diet has been largely neglected. Soy, which is commonly used in the diet in varying quantities can affect their physiology. In order to assess whether the presence of soy can impact the obtained results, we studied the impact of a soy-based diet versus a soy-free diet, on diastolic function in a rat model based on transgenic overexpression of the β(3)-adrenergic receptors in the endothelium and characterized by the appearance of diastolic dysfunction with age. Our results show that the onset of diastolic dysfunction is only observed in transgenic male rats fed with a soy-free diet in the long term. Our study highlights the importance of the diet’s choice in the study design process, especially regarding the proportion of soy, to correctly interpret the outcome as low-cost diets are more likely to be highly concentrated in soy.